Epidemiological susceptibility of slum and non-slum dwellers a discriminant analysis - Abad, Grace R.; Draper, Rolando D. (2012)
This study aimed to analyze slum and non slum dwellers with respect to discriminants on the availability, adequacy and utilization of the source of water supply, type of toilet and type of housing leading to their epidemiological susceptibility to communicable and non communicable diseases. The results showed that there was a significant difference on the water source bought by slum and non slums dwellers compared to the owned and shared deep well, NAWASA and spring. There was also a significant difference seen on the type of toilet particularly on the shared and flush types. The source of water supply and the absence of sanitary toilets among the slum dwellers were found to be significant discriminants in relation to the susceptibility of the respondents to communicable and non-communicable diseases. In particular, susceptibility to these diseases becomes more pronounced among the non-slum dwellers since wastes from the slum areas are carried through the non-slum areas via the water source and unsanitary human waste disposal practices of the slum dwellers.
Keywords: Slums; Mindanao studies; Slum dwellers